Optimization of Land Use in Kuripan Village, Ciseeng District, Bogor Regency - Meisanti Meisanti; Lusi Andriyani; Izzatusholekha Izzatusholekha (Universitas PGRI Semarang, 2023)
Farmers in Kuripan Village cultivate cassava plants. Some farmers plant to get the tubers and others grow to harvest the leaves (oyek). The harvest obtained has not contributed significantly to the income of the farmer's household. For cassava tubers it takes 7 months to harvest while oyek takes a month to harvest. Low prices and market opportunities through middlemen have prevented farmers from relying on their land optimally. As a village assisted by the University of Muhammadiyah Jakarta, the Community Service team provides training to optimized land use by diversifying and regulating cropping patterns to cassava farmers. The targets and outcomes, first, increase the knowledge and skills of farmers to choosing the right plants according to the physical conditions to diversification. Through crop diversification, it will minimize crop failure because more than one type of plant is planted. Second, farmers have skills to design appropriate cropping patterns so the farmers have income continuity throughout the year and loss of soil nutrients at harvest can be minimized so that soil fertility can be save.